In Ladakh Region... Production of microgreen is lucrative - SINGH, Narendra; Maurya, S B; Soni, Vikas; Phour, Manisha; Rani, Seema (Indian Horticulture, 2019)
Microgreen farming is a cultivation of fresh green vegetable plants in soilless light weight reusable growing media in plastic trays as seedling form up to 8-12 cm height and harvested without root within 8-12 days for fresh consumption. These small fresh green plants are rich in flavour, essential phyto-nutrients i.e. proteins, minerals, vitamins and beneficial phyto-bioactive substances for health than their counterparts. By growing and eating these small green plants, communal and wearisome state of mind can be overcome which is a cause of concern in remote locations. By understanding the need of this technique, especially for extremely remote locations and harsh physiographic conditions, where supply of fresh green vegetables is not feasible, techniques have been standardized for growing the different vegetables in tinny form for accessing the quantity of phyto-nutrients to overcome the risk of certain diseases and disorders due to deficiency of essential nutrients in the diet.